The penguin lessons [videorecording (DVD)] - Pope, Jeff; Coogan, Steve; El Jaber, Vivian; Gustafsson, Björn; Carrocio, Alfonsina; Herrero, David; Pryce, Jonathan; Giménez, Xavi, 1970-; Jusid, Federico; Valcárcel, Alberto (Costume designer); Michell, Tom (Sony Pictures, 2025)
Inspired by the true story of a disillusioned Englishman who went to work in a school in Argentina in 1976. Expecting an easy ride, Tom discovers a divided nation and a class of unteachable students. However, after he rescues a penguin from an oil-slicked beach, his life is turned upside-down.